Comparative analysis of a pressure vessel finite element analysis versus speckle photography : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology at Massey University - Wang, Zuping (Massey University, 1994)
A detailed explanation and analysis are presented of the Finite Element Method used to solve the stress/strain situation in a small pressure vessel. A pressure vessel was modelled whose displacement characteristics were previously analysed using speckle photography. The Mystro/Lusas finite element software was used on a PC 486 computer system. A linear and static analysis was made. Contour plots of direct stress and shear stress distribution are presented which also show the highest stress areas. A comparison of the results from Finite Element Method and Speckle Photography Method as well as the pressure vessel design formulas are presented. Advantages of the Finite Element Method are discussed.
Keywords: Pressure vessels -- Design and construction; Pressure vessels -- Testing; Pressure vessels -- Mathematical models; Speckle